Precision Calibration of Robot Magnetorheological Finishing System Based on Laser Tracker - Yujing Wei; Runmu Cheng; Longxiang Li; Qiang Cheng; Yue Pan; Chaoyue Zhu; Jinbo Zhang; Jun Zheng; Bo Ai (Photonics)
Six-degree-of-freedom industrial robots, known for their low cost and high flexibility, have been extensively applied in optical processing. Precise pose control in robot-based optical processing systems depends on the accurate calibration of the tool coordinate system. However, in robot magnetorheological finishing (Robot-MRF) systems, the spherical shape of the polishing wheel poses significant challenges in precisely identifying the working point on the tool’s surface. Traditional calibration methods, such as the four-point or six-point techniques, fail to accurately calibrate the tool coordinate system for MRF tools. To overcome this limitation, a laser tracker-based calibration method is proposed for parameter calibration of the Robot-MRF system. Experimental results show that this method achieves a maximum repeatability error of just 0.0505 mm, significantly improving the stability and reliability of the calibration results and meeting the high-precision processing requirements of MRF technology.